Study of Shear Behavior of Binary Mixtures by DEM Simulation of Biaxial Test in the Membrane Boundary Condition - Wu, Kai; Sun, Weichen; Ding, Jianwen; Zhang, Xiang; Liu, Songyu (Frontiers in Physics, 2021)
This paper aims to study the shear behavior of binary particles with irregular shapes by DEM simulations of the biaxial test in the membrane boundary condition. Binary particle samples are generated according to different volume fractions of coarse and fine particles. The deviatoric stress and volumetric strain curves are plotted to describe the contracting-dilatancy relationship of binary samples under shearing conditions. The anisotropy of the normal and tangential contact forces are explored by visualization of the orientation of contact forces to describe the evolution of micro structures of samples during the shearing process. Besides, the formations of the shear band are observed by the visualization of the newly generated contact force chains between particles. The research shows that the volume fraction of coarse particles and particle size ratio have significant influences on the shear behavior of binary particles both in macroscopic and microscopic points of view. Moreover, the increased volume fraction of coarse particles leads to a more difficult formation of a shear band.